Explorando jogos de língua portuguesa como instrumentos facilitadores na alfabetização de jovens e adultos do campo - Rolim, Aislan Rafael Lemos (2017)
This study aims to present the result of the use of literacy games as a teaching strategy for young people and adults in rural area. For the theoretical basis, we made several readings and reflections from the beginning of adult schooling in the period of colonization to the present day. The literacy conception that guided our study was based on the contributions of Ferreiro; Teberosky (1985), Kleiman (2005), Leal (2004), Morais (2005). When we reflect on the use of playfulness and classroom games in the process of teaching young people and adults, we take into account the studies by Brougere (1998), Oliveira (2016) and Becker (2016). We carried out the pedagogical action project in a school in the Cabo de Santo Agostinho City - PE, specifically in a class with twelve students of Youth and Adult Education. From these twelve students, we selected three who participated in all the proposed activities, to make a comparative analysis between the before and after the practice. At the end of our analysis, we could see an advance in the construction of students' hypotheses of writing from our practice.